Las Vegas Sphere: Technological Innovations that Bring Unforgettable Travel Experiences in the City of Neon Lights - Khairune Nisa, An Nuur (Jurnal Toursci, 2023)
This study aims to show that the uniqueness of Sphere lies not only in its size but also in theadvanced technology that pushes it to new heights. Sphere promises sensations that overwhelm the sensesfor the audience. The integration of cutting-edge technology is not just a feature but an integral part ofSphere's identity, making it more than just a convention entertainment venue. Technology is advancing inthis digital era. Technology also continues to develop, and new things or innovations always appear.Today's generation is very dependent on technology. Almost all aspects of this world, such as work,economy, politics, and entertainment, use various technologies. This study uses a literature approach toexplore specific aspects of technological innovation in the tourism industry. The descriptive method is aconventional approach that involves searching and filtering literature relevant to the chosen topic. Overall,the Las Vegas Sphere provides a comprehensive and immersive tourist experience, combining high-qualityentertainment with innovative technology and architectural design, making it a must-visit attraction in LasVegas. The Las Vegas Sphere, as the latest innovation in the entertainment industry, has had a significantimpact on the tourist experience in Las Vegas and changed the city's image associated with gambling,casinos, and betting.